Atlantic salmon in Arctic aquaculture - enhanced performance, health, and quality with seasonally adjusted dietary protein levels - Turid Mørkøre; Eunice E. Boahemaa-Kobil; Trond M. Kortner; Elvis Chikwati; Vegard Denstadli; Thomas Larsson; Tibiabin Benitez-Santana; Olai Einen (Aquaculture Reports)
This study assessed the effects of periodically increased dietary protein levels (HP diets) on the performance, health, and product quality of Atlantic salmon commercially farmed in 120 m circumference sea-cages in Arctic Finnmark, Norway. Over a one-year trial (October 2021 - October 2022), triplicate cages were fed a Control diet, a HP diet from October–March (HP-W), or from October–July (HP-WS) before returning to the Control diet. HP diets contained 4–5 % more protein than the Control, with comparable energy levels. Fish grew from 570 g to 3.17 kg by October 2022. In March, Control group had the highest prevalence of distal intestinal changes. By July, the Thermal Growth Coefficient was higher for HP-fed groups (3.9) compared to the Control (3.5) (P < 0.01). Compared with the Control group, scale loss was lower of the HP-W, while skin wound prevalence was lower, and slaughter yield was higher of the HP-WS. Fillets from HP-WS were leaner and more intensely colored, with no melanin spots. By October, fillets from HP groups had greater firmness, and fewer melanized muscle segments compared with the Control. Eye lens opacity prevalence was lower in HP groups (4 %) than the Control (23 %; P = 0.03). Fillet yield was lowest in the HP-W group (62.1 %). Across the trial, feed conversion ratio (1.13) and mortality (6.1 %) were unaffected by dietary treatments. This study provides the first evidence that early-phase dietary protein enrichment can enhance resilience, welfare, and fillet quality, mitigating long-term issues like eye defects, soft flesh, gaping, and melanin spots, indicating its potential as a nutritional strategy to enhance production outcomes in Arctic salmon farming.